Can curious employees be more agile? The role of cognitive style and creative process engagement in agility performance - Müceldili, Büşra; Tatar, Berivan; Erdil, Oya (John Wiley and Sons Inc. P.O.Box 18667 Newark NJ 07191-8667, 2020)
Curiosity is an intriguing concept that has attracted the attention of scholars from a variety of disciplines. Yet, work-related curiosity, a crucial factor in workforce agility—the ability of employees to react and adapt to changes in the workplace—has been neglected in organizational research. Here, we broaden our understanding of curiosity in an organizational context through an empirical investigation of the role of cognitive style on work-related curiosity, and the impact of work-related curiosity on the constructs of agility performance and creative process engagement. We argue that cognitive style plays a major role in the formation of work-related curiosity, and hence it is positively associated with agility performance. We also argue that that creative process engagement acts as a mediating factor between work-related curiosity and agility performance. Using structural modeling, and based on data collected from 210 participants in Turkey, we tested five hypotheses concerning these relationships. The results both contribute to the existing literature on work-related curiosity and provide insights for firms wishing to transform their employees' innate curiosity into a valuable organizational resource. © 2020 Elsevier B.V., All rights reserved.